BRAND IMAGE SEBAGAI VARIABEL MEDIATOR PENGARUH GREEN MARKETING TERHADAP LOYALITAS KONSUMEN; KAJIAN EMPIRIS SEBUAH COFFEESHOP GLOBAL DI KOTA BANDUNG - Firdaus, Rani Fadilah; Akhmad Yunani (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to investigate the relationship between green marketing, brand image, and consumer loyalty. Using 255 respondents in Bandung, the results show that green marketing has a positive and significant effect on consumer loyalty, while brand image acts as a mediator variable in this relationship. The results show that green marketing strategies that focus on environmental aspects and brand image can increase consumer loyalty to a brand. This study provides insights for businesses to develop effective green marketing strategies that can increase consumer loyalty and improve their brand image.